Is zakah effective to alleviate poverty in a Muslim society?: A case of Kwara State, Nigeria - Abdussalam O.I.; Johari F.; Alias M. (Kolej University Islam Sultan Azlan Shah, 2024)
Kwara State is one of the Muslim-dominated states in Nigeria, where Islamic economic instrument of zakah is expected to play vital role in alleviating the problem of poverty in the society. One of the objectives of zakah is to economically circulate the wealth and resources from the rich to the poor and eventually realize fair distribution of those wealth and resources in a Muslim society. Therefore, the purpose of this study is to examine the effectiveness of zakah in the poverty reduction of the poor Muslims in Kwara State, Nigeria, particularly, the poor Muslim women. The study employs mixed method of data collection whereby the primary data are explored using the questionnaire and interview designed for the potential respondents during the on-going academic research programme 2013/2014 academic session of 360 sample size. Similarly, verses from Holy Qu'ran and Sunnah of the Prophet Muhammad (pbuh) are used in the study. For the secondary data, existing literature and studies on zakah are also used. Data gathered are analysed using frequencies, percentages and inferential statistics via SPSS 20.0. The findings show that zakah and its institution are not significantly related to and effective in reducing poverty among the poor Muslims in Kwara State, Nigeria. However, recommendations are made towards introduction of standard institution of zakah in the State in order to assist in poverty reduction among the poor Muslims.